EMERGING INFLUENCERS PROMOTING TRAVEL: THE CASE OF LOCAL TOURISM IN LATVIA - Berjozkina, Galina; Garanti, Zanete (Journal of Regional Economic and Social Development, 2021)
The presence of social networks has given a chance for social media influencers to emerge. Social media influencers creating and sharing content, endorsed or not, has become a growing marketing trend used by companies, as well as destinations. This article focuses on travel influencers who, with a help of social networks, particularly Instagram, are promoting local travel in Latvia. In this study, four emerging travel influencers and their posts were retrieved and analysed. The study results show that emerging travel influencers are trying to attract their followers by mostly sharing posts with landscapes and nature, art objects/statues, and nature activities/facilities. However, traditional artwork/objects, religious buildings/objects, and traditional or historic buildings are the pictures achieving the highest engagement rates. Finally, the study also relieved that influencers with a lower number of followers have a higher level of engagement. It is concluded that authenticity and individuality of account, as well as its organic, rather than paid growth, are the key aspects in creating a travel account that followers would engage (like, share and comment on the content). The theoretical and practical implications are discussed.